Additive for low-shrinkage ultra-high performance concrete as well as preparation method and application of additive
The low-shrinkage ultra-high performance concrete admixture addresses shrinkage and cracking issues by using a combination of silica fume, microspheres, and other agents to regulate shrinkage, enhancing compressive strength and durability.
Patent Information
- Application Number
- CN202411473354.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing ultra-high performance concrete admixtures fail to effectively regulate shrinkage and cracking caused by high cementitious material content, leading to poor adaptability and mechanical properties.
A low-shrinkage ultra-high performance concrete admixture comprising silica fume, microspheres, mineral powder, plastic expansion agent, calcium expansion agent, magnesium expansion agent, anhydrite, water-absorbing resin, defoaming agent, and water reducing agent, which synergistically control shrinkage deformation through various stages of concrete hardening.
The admixture reduces internal porosity, enhances compressive strength, improves workability, and compensates for shrinkage at different stages, effectively preventing cracking and improving mechanical properties and durability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to an admixture for low-shrinkage ultra-high performance concrete, a preparation method and an application thereof. Background Art
[0002] Ultra-high performance concrete (UHPC for short) has ultra-high mechanical properties and durability, and is currently the most advanced cement-based composite material. Compared with traditional concrete, ultra-high performance concrete achieves ultra-high mechanical properties and durability by reducing the water-cement ratio, increasing the fiber content, and the most densely packed particles in the mix ratio. However, there are also problems such as high cementitious material content and large cement dosage, which lead to high viscosity and shrinkage of ultra-high performance concrete, which can easily cause through cracking. Therefore, how to prepare excellent admixtures to regulate the shrinkage of ultra-high performance concrete and achieve excellent adaptability of different ground materials, cement and fine aggregates is a difficulty and hot spot in the research and development of ultra-high performance concrete materials. In response to the above problems, Chinese patent applications CN107010860A and CN113860781A respectively disclose methods for preparing ultra-high performance concrete admixtures using solid waste powder, but the prepared admixtures can replace part of the cement, but cannot regulate shrinkage and other problems. Summary of the invention
[0003] Purpose of the invention: In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a low-shrinkage ultra-high performance concrete admixture and a preparation method and application thereof.
[0004] Technical solution: In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0005] A low shrinkage ultra-high performance concrete admixture comprises the following components in parts by weight:
[0006] 15~18 parts of silica fume, 10~15 parts of microspheres, 10~15 parts of mineral powder, 0.3~0.5 parts of plastic expansion agent, 4~6 parts of calcium expansion agent, 4~6 parts of magnesium expansion agent, 3~5 parts of anhydrite, 0.1~0.2 parts of water-absorbing resin, 0.1~0.2 parts of defoaming agent, and 0.5~1 parts of water reducing agent.
[0007] Preferably, the admixture comprises the following components in parts by weight:
[0008] 15 parts of silica fume, 15 parts of microspheres, 10 parts of mineral powder, 5 parts of anhydrite, 0.5 parts of plastic expansion agent, 6 parts of calcium expansion agent, 6 parts of magnesium expansion agent, 0.2 parts of water-absorbing resin, 0.2 parts of defoaming agent, and 0.5 parts of water reducing agent.
[0009] As a specific implementation scheme, the particle size of the silica fume is 0.1-31.3 μm, the silica fume with a particle size less than 1 μm accounts for 33.3-100%, and the content of SiO2 is ≥95%.
[0010] As a specific implementation scheme, the sum of the SiO2 and Al2O3 contents in the micro-beads is greater than 85wt%, the ignition loss is ≤3%, and the particle size of the micro-beads is 0.1 to 98.1 μm.
[0011] As a specific implementation scheme, the specific surface area of the mineral powder is 500~700m 2 / kg.
[0012] As a specific implementation scheme, the plastic expansion agent is a mixture of p-nitrobenzene diazonium fluoroborate and iminodiacetonitrile, and the mass ratio of p-nitrobenzene diazonium fluoroborate to iminodiacetonitrile in the mixture is (2-4):(6-8).
[0013] As a specific implementation scheme, the preparation method of the calcium expansion agent comprises the following steps:
[0014] The limestone and gypsum are mixed and ground into powder, calcined at 1100-1300°C for 60-120 minutes, and then ground into powder together with zeolite powder and fly ash to obtain a calcium oxide expansion agent; the free calcium oxide in the obtained calcium oxide expansion agent is not less than 55%.
[0015] As a specific implementation scheme, the magnesium expansion agent is a mixture of magnesium oxides with different activities generated by using magnesite as raw material under different calcination temperatures and calcination times; the calcination temperature is 750-850°C, and the calcination time is 120s-300s.
[0016] As a preferred embodiment, the magnesium expansion agent is a mixture of different active magnesium oxides generated by using magnesite as raw material at a calcination temperature of 750-850°C and a calcination time of 120s, 180s and 240s respectively; the mass ratio of different active magnesium oxides is MgO 120s : MgO 180s : MgO 240s =(2~4):(2~4):(3~5).
[0017] As a specific implementation, the water-absorbing resin is selected from one or a combination of sodium polyacrylate, polyacrylamide, and polyacrylonitrile.
[0018] As a specific implementation scheme, the defoaming agent is selected from one or more of polyether defoaming agents, modified lipid defoaming agents, and high-carbon alcohol compounds.
[0019] As a specific implementation, the water reducer is selected from polycarboxylic acid water reducer with a water reduction rate of ≥30%.
[0020] The present invention also provides a method for preparing the low-shrinkage ultra-high performance concrete admixture, comprising the following steps:
[0021] The calcium expansion agent and the magnesium expansion agent are calcined respectively to obtain powders;
[0022] The low shrinkage ultra-high performance concrete admixture is obtained by mixing the above-mentioned powder, silica fume, microbeads, mineral powder, plastic expansion agent, anhydrite, water-absorbing resin, defoaming agent and water reducing agent.
[0023] Finally, the present invention provides the application of the admixture in the preparation of low shrinkage ultra-high performance concrete.
[0024] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0025] The present invention adopts silica fume, microspheres, mineral powder, plastic expansion agent, calcium expansion agent, magnesium expansion agent, anhydrite, water-absorbing resin, defoaming agent, water reducing agent and multiple raw materials to control the shrinkage deformation of ultra-high performance concrete. The glass body of silica fume and microspheres has excellent ball effect, which improves the working performance. Its unique volcanic ash effect and micro-aggregate effect, ultra-fine silica powder can fill the gap between particles, improve the density and plastic viscosity, and reduce the segregation rate. The generated product can reduce the internal porosity, increase the density and later strength of concrete, and the introduction of mineral powder can further promote the ultra-high performance concrete. The hydration reaction of soil can improve the compressive strength at different ages; the synergistic effect of plastic expansion agent, anhydrite, calcium expansion agent, magnesium expansion agent and water-absorbing resin can be used in the early, middle and late stages of the plastic stage and hardening stage of concrete, and at the same time can reduce the drying shrinkage deformation. The specific control principle is that the volume expansion of anhydrite and plastic expansion agent occurs after water, and the synergistic effect of the two can compensate for the shrinkage of the plastic stage of concrete. The calcium expansion agent is used to compensate for the early shrinkage of 1 to 3 days after hardening, and the magnesium expansion agent with different activities is used to compensate for the mid-term and late shrinkage. The water-absorbing resin compensates for the late drying shrinkage. After using defoamers and polycarboxylic acid water-reducing agents, water consumption can be reduced, flow properties can be improved, and air content can be reduced, which is helpful to improve the mechanical properties and durability of concrete. The low-shrinkage ultra-high performance concrete of the present invention has excellent adaptability. On the one hand, it can improve the compressive strength and workability of different ages. On the other hand, it effectively solves the problems of large shrinkage and easy cracking of concrete caused by the high amount of cementitious materials and cement dosage of traditional ultra-high performance concrete. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The raw materials used in the following examples and comparative examples are as follows:
[0028] The particle size of silica fume is 0.1~31.3μm, the silica fume with a particle size less than 1μm accounts for 40%, and the SiO2 content is 98%.
[0029] The total content of SiO2 and Al2O3 in the micro-beads is 89wt%, the ignition loss is 2%, and the particle size of the micro-beads is 0.1-98.1μm.
[0030] The specific surface area of the mineral powder is 700m 2 / kg.
[0031] The plastic expansion agent is a mixture of p-nitrobenzene diazonium fluoroborate and iminodiacetonitrile, wherein the mass ratio of p-nitrobenzene diazonium fluoroborate to iminodiacetonitrile in the mixture is 3:7.
[0032] The preparation method of the calcium expansion agent comprises the following steps:
[0033] The limestone and gypsum are mixed and ground into powder, calcined at 1100°C for 90 minutes, and then ground into powder together with zeolite powder and fly ash to obtain a calcium oxide expansion agent; the free calcium oxide in the obtained calcium oxide expansion agent is not less than 55%.
[0034] Magnesium expansion agent is a mixture of different active magnesium oxides produced by calcining magnesite at 800℃ for 120s, 180s and 240s respectively. The mass ratio of different active magnesium oxides is MgO 120s : MgO 180s MgO 240s =3:3:4.
[0035] The water-absorbing resin is selected from sodium polyacrylate; the defoaming agent is a polyether defoaming agent; and the water reducing agent is a polycarboxylic acid water reducing agent with a water reducing rate of 30%.
[0036] The silica fume comes from Zibo Boken Silica Materials Co., Ltd.; the microbeads and mineral powder come from Zhenjiang Boya Building Materials Co., Ltd.; the water-absorbing resin, defoaming agent, polycarboxylic acid water-reducing agent, etc. come from BASF (China) Co., Ltd.
[0037] Example 1
[0038] The admixture includes the following components in parts by weight:
[0039] 15 parts of silica fume, 15 parts of microspheres, 10 parts of mineral powder, 5 parts of anhydrite, 0.5 parts of plastic expansion agent, 6 parts of calcium expansion agent, 6 parts of magnesium expansion agent, 0.2 parts of water-absorbing resin, 0.2 parts of defoaming agent, and 0.5 parts of water reducing agent.
[0040] The preparation method is as follows:
[0041] The ground and calcined calcium expansion agent and magnesium expansion agent are mixed with silica fume, microbeads, mineral powder, plastic expansion agent, anhydrite, water-absorbing resin, defoaming agent and polycarboxylic acid water-reducing agent according to the above weight proportions, and stirred in a mixer at a speed of 100 rpm for 15 minutes.
[0042] Example 2
[0043] The admixture includes the following components in parts by weight:
[0044] 15 parts of silica fume, 10 parts of microspheres, 10 parts of mineral powder, 0.3 parts of plastic expansion agent, 4 parts of calcium expansion agent, 4 parts of magnesium expansion agent, 3 parts of anhydrite, 0.1 parts of water-absorbing resin, 0.1 parts of defoaming agent, and 0.5 parts of water reducing agent.
[0045] The preparation method is as follows:
[0046] The ground and calcined calcium expansion agent and magnesium expansion agent are mixed with silica fume, microbeads, mineral powder, plastic expansion agent, anhydrite, water-absorbing resin, defoaming agent and polycarboxylic acid water-reducing agent according to the above weight proportions, and stirred in a mixer at a speed of 100 rpm for 15 minutes.
[0047] Example 3
[0048] The admixture includes the following components in parts by weight:
[0049] 18 parts of silica fume, 15 parts of microspheres, 15 parts of mineral powder, 0.5 parts of plastic expansion agent, 6 parts of calcium expansion agent, 6 parts of magnesium expansion agent, 5 parts of anhydrite, 0.2 parts of water-absorbing resin, 0.2 parts of defoaming agent, and 1 part of water reducing agent.
[0050] The preparation method is as follows:
[0051] The ground and calcined calcium expansion agent and magnesium expansion agent are mixed with silica fume, microbeads, mineral powder, plastic expansion agent, anhydrite, water-absorbing resin, defoaming agent and polycarboxylic acid water-reducing agent according to the above weight proportions, and stirred in a mixer at a speed of 100 rpm for 15 minutes.
[0052] Comparative Example 1
[0053] The difference between this comparative example and Example 1 is that no plastic expansion agent and anhydrite are added, and the weight proportions thereof are replaced by microspheres.
[0054] Comparative Example 2
[0055] The difference between this embodiment and embodiment 1 is that no plastic expansion agent is added, and the weight portion is replaced by micro beads.
[0056] Comparative Example 3
[0057] The difference between this embodiment and embodiment 1 is that anhydrite is not added, and the weight portion is replaced by microspheres.
[0058] Comparative Example 4
[0059] The difference between this embodiment and embodiment 1 is that no plastic expansion agent, anhydrite and calcium expansion agent are added, and the weight proportions thereof are replaced by microspheres.
[0060] Comparative Example 5
[0061] The difference between this embodiment and embodiment 1 is that no plastic expansion agent, anhydrite and magnesium expansion agent are added, and the weight proportions thereof are replaced by microspheres.
[0062] Comparative Example 6
[0063] The difference between this embodiment and embodiment 1 is that no plastic expansion agent, anhydrite, calcium expansion agent, and magnesium expansion agent are added, and the weight proportions thereof are replaced by microspheres.
[0064] Comparative Example 7
[0065] The difference between this embodiment and embodiment 1 is that no water-absorbing resin is added, and the weight portion is replaced by micro beads.
[0066] Comparative Example 8
[0067] The difference between this embodiment and embodiment 1 is that no plastic expansion agent, hard gypsum and water-absorbing resin are added, and the weight proportions are replaced by microbeads.
[0068] Comparative Example 9
[0069] The difference between this comparative example and Example 1 is that no plastic expansion agent, anhydrite, calcium expansion agent, magnesium expansion agent, and water-absorbing resin are added, and the weight portions thereof are replaced by microbeads.
[0070] Comparative Example 10
[0071] The difference between this comparative example and Example 1 is that the 180S and 240S components in the magnesium expansion agent are not added, and both components are replaced by the 120S component.
[0072] Comparative Example 11
[0073] The difference between this comparative example and Example 1 is that the 120S and 240S components in the magnesium expansion agent are not added, and both components are replaced by the 180S component.
[0074] Comparative Example 12
[0075] The difference between this comparative example and Example 1 is that the 120S and 180S components in the magnesium expansion agent are not added, and both components are replaced by the 240S component.
[0076] The ultra-high performance concrete admixtures prepared in the examples and comparative examples were tested according to the testing methods of GB / T31387-2015 and GB / T50081-2019. The test mix ratios and test results are shown in Tables 1 and 2, respectively.
[0077] Table 1 Test mix ratio
[0078]
[0079] Table 2 Test results
[0080]
[0081] Note: Positive values represent slight overall expansion, negative values represent overall contraction.
[0082] The test results of admixtures for low shrinkage ultra-high performance concrete show that: according to the test results of comparative examples 5 and 8, although the compressive strength of the traditional ultra-high performance concrete admixture can meet the requirements, the early 6h, 24h shrinkage and 3d / 7d28d shrinkage are very large, which also leads to the problem of easy cracking of the traditional ultra-high performance concrete. In contrast, the present invention uses an admixture prepared from a variety of raw materials including silica fume, microbeads, mineral powder, plastic expansion agent, anhydrite, calcium expansion agent, magnesium expansion agent, water-absorbing resin, defoaming agent, and polycarboxylic acid water-reducing agent to prepare ultra-high performance concrete in a certain proportion. The concrete not only has good mechanical properties, but also can be effectively compensated at different shrinkage stages of 6h, 24h and 3d / 7d / 28d, achieving a micro-expansion effect.
[0083] The implementation modes of the present invention have been described in detail above in conjunction with specific embodiments, but the present invention is not limited to the above-mentioned implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A low shrinkage ultra-high performance concrete admixture, characterized in that: The composition comprises the following components in parts by weight: 15~18 parts of silica fume, 10~15 parts of microspheres, 10~15 parts of mineral powder, 0.3~0.5 parts of plastic expansion agent, 4~6 parts of calcium expansion agent, 4~6 parts of magnesium expansion agent, 3~5 parts of anhydrite, 0.1~0.2 parts of water-absorbing resin, 0.1~0.2 parts of defoaming agent, and 0.5~1 parts of water reducing agent.
2. The low shrinkage ultra-high performance concrete admixture according to claim 1, characterized in that: The admixture comprises the following components in parts by weight: 15 parts of silica fume, 15 parts of microspheres, 10 parts of mineral powder, 5 parts of anhydrite, 0.5 parts of plastic expansion agent, 6 parts of calcium expansion agent, 6 parts of magnesium expansion agent, 0.2 parts of water-absorbing resin, 0.2 parts of defoaming agent, and 0.5 parts of water reducing agent.
3. The low shrinkage ultra-high performance concrete admixture according to claim 1 or 2, characterized in that: The particle size of the silica fume is 0.1-31.3 μm, the proportion of silica fume with a particle size less than 1 μm is 33.3-100%, and the content of SiO2 is ≥95%; the sum of the content of SiO2 and Al2O3 in the microspheres is greater than 85wt%, the loss on ignition is ≤3%, and the particle size of the microspheres is 0.1-98.1 μm; the specific surface area of the mineral powder is 500-700m 2 / kg.
4. The low shrinkage ultra-high performance concrete admixture according to claim 1, characterized in that: The plastic expansion agent is a mixture of p-nitrobenzene diazonium fluoroborate and iminodiacetonitrile, and the mass ratio of p-nitrobenzene diazonium fluoroborate to iminodiacetonitrile in the mixture is (2-4): (6-8).
5. The low shrinkage ultra-high performance concrete admixture according to claim 1, characterized in that: The preparation method of the calcium expansion agent comprises the following steps: The limestone and gypsum are mixed and ground into powder, calcined at 1100-1300°C for 60-120 minutes, and then ground into powder together with zeolite powder and fly ash to obtain a calcium oxide expansion agent; the free calcium oxide in the obtained calcium oxide expansion agent is not less than 55%.
6. The low shrinkage ultra-high performance concrete admixture according to claim 1, characterized in that: The magnesium expansion agent is a mixture of magnesium oxides with different activities generated by using magnesite as raw material under different calcination temperatures and calcination times; the calcination temperature is 750-850° C., and the calcination time is 120s-300s.
7. The low shrinkage ultra-high performance concrete admixture according to claim 1, characterized in that: The magnesium expansion agent is a mixture of different active magnesium oxides produced by using magnesite as raw material at a calcination temperature of 750-850°C and a calcination time of 120s, 180s and 240s respectively; the mass ratio of the different active magnesium oxides is MgO 120s : MgO 180s : MgO 240s =(2~4):(2~4):(3~5).
8. The low shrinkage ultra-high performance concrete admixture according to claim 1, characterized in that: The water-absorbing resin is selected from one or a combination of sodium polyacrylate, polyacrylamide, and polyacrylonitrile; the defoamer is selected from one or more of polyether defoamers, modified lipid defoamers, and high-carbon alcohol compounds; and the water reducer is selected from polycarboxylic acid water reducers with a water reduction rate of ≥30%.
9. The method for preparing the low shrinkage ultra-high performance concrete admixture according to any one of claims 1 to 8, characterized in that: The steps include: The calcium expansion agent and the magnesium expansion agent are calcined respectively to obtain powders; The low shrinkage ultra-high performance concrete admixture is obtained by mixing the above-mentioned powder, silica fume, microbeads, mineral powder, plastic expansion agent, anhydrite, water-absorbing resin, defoaming agent and water reducing agent.
10. Use of the admixture according to any one of claims 1 to 8 in the preparation of low shrinkage ultra-high performance concrete.
Citation Information
Patent Citations
High-performance concrete expansion agent and preparation method thereof
CN102329093A
Anti-cracking admixture for strong-constraint composite wall lining concrete
CN110655344A
Ultra-high-stroke pumping anti-crack concrete suitable for cable bent tower structure and preparation method
CN111848019A
Large-flow-state micro-expansion ultra-high performance concrete and preparation method thereof
CN116813275A
Mineral admixture for ultra-high performance concrete and preparation method thereof
CN117361934A
Cited By
Large-flow-state crack-resistant ultrahigh-toughness cement-based composite material and preparation method thereof
CN120965225A
A high-flow-state crack-resistant ultra-high toughness cement-based composite material and its preparation method
CN120965225B